2011
DOI: 10.1007/s10157-011-0525-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of serum cystatin C versus serum creatinine as a marker of glomerular filtration rate as measured by inulin renal clearance

Abstract: The performance of serum cystatin C was not good in the subjects with very low GFR. Non-renal elimination of cystatin C may contribute to the result. The correlation between reciprocal cystatin C and GFR suggested its superiority in predicting GFR compared to creatinine in subjects with normal and mildly reduced GFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
1
31
0
3
Order By: Relevance
“…These discrepancies are attributed primarily to differences in creatinine production since the muscle mass of women is approximately 15% smaller than that of men (65,66). However, measured GFR (using inulin) is also lower in healthy women than in men (67), suggesting that physiological differences within the kidney may also contribute to gender differences in GFR.…”
Section: Gendermentioning
confidence: 99%
“…These discrepancies are attributed primarily to differences in creatinine production since the muscle mass of women is approximately 15% smaller than that of men (65,66). However, measured GFR (using inulin) is also lower in healthy women than in men (67), suggesting that physiological differences within the kidney may also contribute to gender differences in GFR.…”
Section: Gendermentioning
confidence: 99%
“…Female gender was associated with lower Scys-C in young subjects ( P <0.001), but in the elderly, it was not an influencing factor ( P  = 0.836). Some studies revealed that Scys-C was influenced by gender, while Yashiro et al reported that Scys-C levels were not gender-related [10], [11], [12]. Decreased secretion of sex hormone in the elderly may contribute the difference between these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated that many factors other than renal function may influence Scys-C, and more studies are needed for verification [10], [11], [12]. Multivariate linear regression analysis was conducted in three groups, all subjects, the young and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Volt olyan is, amely szerint anorexia nervosában egyik sem volt használható a GFR becslésére [26]. Hasonló volt a helyzet 125 I-iothalamát, iohexol és inulin -mint "arany standardok" -esetében is [27,28,29]. A 99m Tc-DPTA-val végzett tanulmányok a cisztain-C-vel meghatározott eGFR-eket találták valósabbnak az MDRDegyenlettel összehasonlítva [30].…”
Section: Megbeszélésunclassified